Impact of Corporate Social Responsibility, Business Ethics and Corporate Reputation on the Retention of Users of Third-Sector Institutions - Cabrera-Luján, Samuel Leroy (2023)
Third-sector organizations have achieved an important place in the world due to the multiple social and humanitarian activities they carry out, generating a high impact on society. Maintaining their sustainability basically depends on the retention of their users, but what factor could contribute to this retention? To dispel this question, the purpose of the study is to understand corporate social responsibility (CSR), business ethics (BE) and corporate reputation (CR), and their connections with user retention (RT). Using structural equation analysis (SEM) and non-probabilistic sampling, 501 users of third-sector organizations (199 Uruguay and 302 Peru) were surveyed. The results show a positive and significant impact of CSR on CR, influence of BE on CR, effect of CSR on RT, effect of CR and BE on RT. It is highlighted that CR would have a greater effect on RT and BE, followed by CSR. It is concluded that CR represents a very important and sensitive value at the same time, which is a characteristic that takes a long time to achieve, so it is important to manage it properly, being the one that contributes most to RT.